Auditoría ambiental de seguimiento de la estación de servicio El Guabo, año 2021 - Maldonado Villalta, Yanela Cristina (My University, 2021)
The Environmental Compliance Audit of the El Guabo Service Station was carried out in order to verify the level of compliance with the Environmental Management Plan and the Current Environmental Regulations. The methodology used for the development of the Environmental Compliance Audit is made up of three stages, the first is the pre-audit where a series of procedures is carried out such as the review of the Environmental Management Plan by the audit team, the assignment of tasks, and the pre-audit meeting, then comes the on-site audit where work is already carried out directly in the field and where the information will be collected to demonstrate whether the service station has adequate control of its facilities, and the last stage is the post-audit where environmental reports are made and results are obtained. Once this process has been carried out and the findings of non-compliance have been identified, the Action Plan is executed, which contains the corrective measures to minimize these impacts. The Service Station has a level of compliance with the Environmental Management Plan of 87.5% and the Environmental Regulations in force in Ecuador of 100%, it is important that they comply with the Action Plan taking into account the established time and taking evidence.
La Auditoría Ambiental de Cumplimiento de la Estación de Servicios El Guabo, se realizó con el motivo de verificar el nivel de cumplimiento del Plan de Manejo Ambiental y de la Normativa Ambiental Vigente. La metodología que se utilizó para el desarrollo de la Auditoría Ambiental de Cumplimiento está conformada por tres etapas, la primera es la pre-auditoría en donde se realiza una serie de procedimientos como la revisión del Plan de Manejo Ambiental por parte del equipo auditor, la designación de tareas, y la reunión de pre-auditoría, luego viene la auditoría in-situ en donde ya se procede a trabajar directamente en el campo y donde se levantará la información que permita demostrar si la estación de servicios lleva el control adecuado de sus instalaciones, y la última etapa es la post-auditoría en donde se realizan los informes ambientales y se obtienen resultados. Una vez realizado este proceso y de haber identificado los hallazgos de incumplimiento, se ejecuta el Plan de Acción en donde constan las medidas correctoras para minimizar estos impactos. La Estación de Servicios cuenta con un nivel de cumplimiento del Plan de Manejo Ambiental de un 87,5% y de la Normativa Ambiental Vigente en el Ecuador de un 100%, es importante que den cumplimiento al Plan de Acción tomando en cuenta el tiempo establecido y la toma de evidencias.
Keywords: PLAN DE MANEJO; MEDIDA CORRECTORA; PLAN DE ACCION; AUDITORIA AMBIENTAL